Monsoon‐Frontal Interactions Drive Cyclone Biparjoy's Wake Recovery in the Arabian Sea - Siddhant Kerhalkar; Ankitha Kannad; Alex Kinsella; Amit Tandon; Janet Sprintall; Craig M. Lee (Geophysical Research Letters)
Abstract Cyclone‐generated cold wakes enhance productivity and impact local air‐sea interaction, paths and intensities of subsequent storms in the region. However, in‐situ observations of recovery across such wakes are rare. A cold wake in the Arabian Sea was surveyed using multiple shipboard instruments approximately 10 days after the passage of Cyclone Biparjoy in 2023. The wake, nearly 30 km wide, had a stronger (weaker) buoyancy gradient at its eastern (western) edge and assumed a downfront (upfront) orientation relative to the southwesterly monsoon winds. This resulted in notable asymmetry in the vertical structure of temperature, salinity and velocity at the edges of the wake, indicating the importance of Ekman Buoyancy Fluxes and Mixed Layer Eddies. While the wake recovery following a cyclone is often attributed to one‐dimensional diurnal heating and cooling, these observations underscore the role of interactions between monsoon winds and underlying three‐dimensional submesoscale processes for a slow‐moving cyclone wake recovery.